2010
DOI: 10.2113/gsrocky.45.2.83
|View full text |Cite
|
Sign up to set email alerts
|

Geologic carbon sequestration in Wyoming: prospects and progress

Abstract: Coal supplies nearly 50 percent of electricity generation in the United States and 25 percent of the global energy supply; Wyoming produces approximately 40 percent of the coal consumed in the United States. It is likely that near-term energy strategies will include coal and other fossil energy sources in the fuel mix, therefore mitigating carbon dioxide emissions through geologic carbon capture and sequestration (CCS) is crucial. Here we discuss the current state of CCS technology across the globe and its fut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Another group totalling 68 papers (8%) addressed storage site assessments and storage potentials. Key papers included Wei et al [28] (d = 90), who developed a framework for the evaluation of storage site suitability, in which the authors took into account storage capacity optimisation, injectivity, risk minimisation, storage security, environmental restrictions, and economic issues; Civile et al [29] (d = 71), who identified and characterised areas potentially suitable for CO 2 geological storage at a regional scale in carbonate rocks in Italy; and Frost and Jakle [30] (d = 70), who characterised areas of Palaeozoic deep saline aquifers in the Rocky Mountain West.…”
Section: The Base Paper Networkmentioning
confidence: 99%
“…Another group totalling 68 papers (8%) addressed storage site assessments and storage potentials. Key papers included Wei et al [28] (d = 90), who developed a framework for the evaluation of storage site suitability, in which the authors took into account storage capacity optimisation, injectivity, risk minimisation, storage security, environmental restrictions, and economic issues; Civile et al [29] (d = 71), who identified and characterised areas potentially suitable for CO 2 geological storage at a regional scale in carbonate rocks in Italy; and Frost and Jakle [30] (d = 70), who characterised areas of Palaeozoic deep saline aquifers in the Rocky Mountain West.…”
Section: The Base Paper Networkmentioning
confidence: 99%
“…The RSU, located in Southwestern Wyoming (Figure 1), has been identified as a potential geologic CO 2 storage site in Southwestern Wyoming (Campbell-Stone et al, 2011;Frost & Jakle, 2010;Grana et al, 2017;Surdam, 2013). Formed during the Late Cretaceous to Paleogene Laramide Orogeny (Erslev & Koenig, 2009), the RSU is an asymmetric, doubly plunging anticline with more than 3,000 m of closed structural relief that lies on the Rocky Mountain foreland basement.…”
Section: Reservoir Setting Of the Rsu Wyomingmentioning
confidence: 99%
“…This site was also of interest for sequestration research activities due to a large abundance of natural CO 2 being produced as a byproduct of oil and gas development in the region and an already present CO 2 sequestration infrastructure and market to support enhanced oil recovery (EOR). These two factors provide both a potential supply of CO 2 and future opportunities for CCS (Frost and Jakle, 2010).…”
Section: Study Areamentioning
confidence: 99%